Comparison of Anesthetic Properties of Ketofol (Ketamine with Propofol) and Propofol in Minor Surgical Procedures - Karki, Shambhu Bahadur; Rajbanshi, Lalit Kumar; Arjyal, Bastalya; Khanal, Kanak (Birat Journal of Health Sciences, 2018)
Introduction: Outpatient anesthesia for the minor day care surgical procedures requires a safe anesthesia and anesthetic agents. For this purpose two study solutions propofol with ketamine (ketofol) and propofol were compared. The comparison of the both agents were assessed, evaluated and discussed in this study. Methodology: This is prospective study of 100 adult patients of both sex aged between 18-60 years with ASA physical status class I and II who were operated in the Birat Medical College teaching hospital. This study was started after approval from the ethical committee of the hospital and after written and informed consent from all participants. All patients were randomly divided into two groups. Group A (n=50) received ketamine with propofol and Group B (n=50) propofol after intravenous sedation with 2 mg of midazolam and 1 mg of butorphanol. The main aim of this study was comparison of onset of sedation, respiratory and cardiac adverse events, level of sedation using Ramsey sedation scale, requirement of sedatives, recovery time, average cost of the sedatives and postoperative complications between the two groups. All collected data are analyzed using MS Excel office 2007 and for the data analysis IBM SPSS software was used.Results: In the both groups patients were comfortable with the either anesthetic agents. Onset of anesthesia was faster in Group A. Intraoperative sedation was measured using Ramsay sedation scale and was comparable. Recovery from sedation was assessed with AVPU scale and patient was shifted to postoperative room after the verbal response. Postoperative complications seen were nausea vomiting, severe pain, ketamine induced psychotomimetic effects and all of these were treated well and discharged on the same day from the hospital.Conclusion: The combination of ketamine and propofol for the sedation in minor surgical procedures has more advantages than the propofol alone. The combination is cost effective, has better sedation and hemodynamic stability, quick recovery and fewer side effects in the post operative room. Birat Journal of Health SciencesVol.2/No.3/Issue 4/Sep- Dec 2017, Page: 287- 291